Frequency Regulation for High Wind Penetration Power System Based on Ocean Predator Algorithm Considering Storage Battery State - Yingjie Hu; Chenggen Wang; Xiaoming Zou (Energies)
The high penetration and uncertainty of renewable energy sources, such as wind, in modern power systems make traditional automatic generation control (AGC) methods more challenging. In order to improve the frequency stability of the power system under the high proportion of wind power penetration, the inherent fast-response characteristics of energy storage allow bidirectional adjustments with the system. However, storage power becomes insufficient when the state of charge (SOC) approaches its upper or lower limits, at this time, it is difficult to take into account both the state of charge protection of the energy storage and the effect of frequency regulation. Based on the purpose of testing the grid frequency containment reserve (FCR) performance and efficient use of frequency modulation resources, this paper proposes a wind power high penetration system frequency modulation control strategy considering the storage state of charge by constructing a two-zone automatic generation control system model containing wind power, using an improved adaptive ocean predator algorithm to optimise the frequency modulation responsibility allocation method in real time, and formulating a real-time management scheme for storage state of charge. Finally, the different control strategies are compared and analysed by MATLAB 2018b/Simulink under different loads and wind speeds, and their effectiveness is verified by the frequency offset and state of charge offset, so as to optimise the effect of frequency modulation while maintaining the state of charge of energy storage.